Influence of a pulsed laser regime on surface finish induced by the direct metal deposition process on a Ti64 alloy - Gharbi, Myriam; Peyre, Patrice; Gorny, Cyril; Carin, Muriel; Morville, Simon; Le Masson, Philippe; Carron, Denis; Fabbro, Rémy (Journal of materials processing technology, 2014)
The direct metal deposition (DMD) laser technique is a free-form metal deposition process, which allows generating a prototype or small series of near net-shape structures. Despite numerous advantages, one of the most critical issues of the technique is that produced pieces have a deleterious surface finish which requires post machining steps. Following recent investigations where the use of laser pulses instead of a continuous regime was successful to obtain smoother DMD structures, this paper relates investigations on the influence of a pulsed laser regime on the surface finish induced by DMD on a widely used titanium alloy (Ti64). Findings confirm that using high mean powers improves surface finish but also indicate a specific effect of the laser operating mode: using a quasi-continuous pulsed mode instead of fully-cw laser heating is an efficient way for surface finish improvement. For similar average powers, the use of a pulsed mode with large duty cycles is clearly shown to provide smoothening effects. The formation of larger and stable melt pools having less pronounced lateral curvatures, and the reduction of thermal gradients and Marangoni flow in the external side of the fusion zone were assumed to be the main reasons for surface finish improvement. Additional results indicate that combining the benefits from a pulsed regime and a uniform laser irradiation does not provide further reduction of surface roughness.